Selection of Sport- and Racehorses - Mihók, Sándor (Acta Agraria Debreceniensis, 2005)
The utilisation of the horse has changed from time to time in response to human needs. For a few decades, it has been serving in several equestrian sports more intensively. It has also been proved that the standards for this kind of performance cannot be established in the way certain characteristics, such as the weight gain or milk production of other animal breeds can. Breeding horses for sporting comprises highly complex selection criteria.Some of these (e.g. external features, temperament, manageability and intelligence) do not put the breeder in a difficult position, but finding the traits that establishes the safety of sporting achievements poses a genetic problem.The performance of a horse for sports is a highly complex feature, which cannot easily be assessed or put down in figures. In addition, man plays a decisive role in shaping all kinds of performance of a horse at any given time by not only creating conditions for a better performance, but also by playing an active role in increasing it.The performance of the horse is mostly defined by its general aptitude to movement, ie., the regularity, clear rhythm and springiness of basic types of strides, as well as the ability to move in a naturally balanced way. Training and riding principles are based on these traits. These two together will determine about 70% of the value of the horse and its adequacy for high performance equestrian sports. In order to avoid subjectivity in determining the above variables and to increase the degree of objectivity, competent expert teams (trainers, judges, other riders) are employed to form an opinion on an individual animal.Assessing horse performance outside races does not seem to be efficient, as owing to the dominant effects of the environment, the indicator of inheritability is hardly above 0.1.Free jumping is an especially appropriate means for assessing a horse’s readiness and ability to move in an environment free of disturbing factors. In free jumping, it is especially important to judge the style of the jump. The first phase of jumping – as a sequence of movements – lasts from the moment the fore-feet touch the ground until the moment the hind-feet push off, while the second phase lasts from this moment until touching the ground. The most important task in the first phase is to make the angle of the dip of the body by the supporting fore-feet that is necessary for the jump. The quality of the jump is determined by the jumping and adequately expanded hind-legs. The intensity of pushing off and jumping done by the hind-legs can be inferred, and differences between individuals can be discerned from the shaping of the curve by the hocks and the paths of the pasterns in relation to the withers.